Past and next 10 years of medical informatics - Uckert, F.; Ammenwerth, Elske; Dujat, C.; Grant, A.; Haux, Reinhold; Hein, A.; Hochlehnert, A.; Knaup-Gregori, Petra; Kulikowski, C.; Mantas, J.; Maojo, V.; Marschollek, M.; et al. (J Med Syst, 2014)
More than 10 years ago Haux et al. tried to answer the question how health care provision will look like in the year 2013. A follow-up workshop was held in Braunschweig, Germany, for 2 days in May, 2013, with 20 invited international experts in biomedical and health informatics. Among other things it had the objectives to discuss the suggested goals and measures of 2002 and how priorities on MI research in this context should be set from the viewpoint of today. The goals from 2002 are now as up-to-date as they were then. The experts stated that the three goals: \textquotedblpatient-centred recording and use of medical data for cooperative care\textquotedbl; \textquotedblprocess-integrated decision support through current medical knowledge\textquotedbl and \textquotedblcomprehensive use of patient data for research and health care reporting\textquotedbl have not been reached yet and are still relevant. A new goal for ICT in health care should be the support of patient centred personalized (individual) medicine. MI as an academic discipline carries out research concerning tools that support health care professionals in their work. This research should be carried out without the pressure that it should lead to systems that are immediately and directly accepted in practice.